The effect of osteopathic medicine on pain in musicians with nonspecific chronic neck pain: a randomized controlled trial. (December 2020) - Rotter, Gabriele; Fernholz, Isabel; Binting, Sylvia; Keller, Theresa; Roll, Stephanie; Kass, Benjamin; Reinhold, Thomas; Willich, Stefan N.; Schmidt, Alexander; Brinkhaus, Benno
Background: Nonspecific chronic neck pain (cNP) is common in adult violinists and violists and is often treated with osteopathic medicine (OM), although the effectiveness of this treatment has not been determined to date. This study aimed to evaluate the effectiveness and safety of OM in adult violinists and violists with cNP. Methods: In a two-armed randomized controlled single-center open trial, adult violinists and violists, including music students, with cNP (⩾12 weeks) were randomized to either five individualized OM sessions (OM group) or to no intervention (control group, CG) in the outpatient clinic for integrative medicine, Charité - Universitätsmedizin Berlin, Germany. All patients received a musicians' medicine consultation and paracetamol on demand. The primary outcome parameter was the neck pain intensity on a visual analog scale (VAS, 0–100 mm, 0 = no pain, 100 = worst imaginable pain) after 12 weeks. Secondary outcomes included neck pain disability (Neck Disability Index, NDI, 0–100%) after 12 weeks. The last follow-up visit was after 52 weeks. Statistical analysis included analysis of covariance adjusted for respective baseline value. Results: Altogether, 62 outpatients were included [OM group ( n = 28), CG ( n = 34); 81% female; mean age, 41.6 ± 11.1 years; mean baseline neck pain, 55.9 ± 11.6 mm]. After 12 weeks, OM was associated with an improvement in the OM group versus the CG in neck pain on the VAS [14.6 mm (95% confidence interval 8.0; 21.2) versus 40.8 mm (34.7; 46.9), p < 0.001, Cohen's d = 1.4], and neck pain disability as determined by the NDI [8.8% (6.7; 10.8) versus 17.2% (15.3; 19.1), p < 0.001]. Some improvements were maintained until 52 weeks of follow-up. No serious adverse events were observed. Conclusions: The results of this study suggest that OM might be effective in reducing pain intensity in adult violinists and violists with nonspecific cNP. Further studies should investigate the efficacy of OM in comparison with a sham procedure and with other effective therapy methods in high-quality multicenter trials. Trial registration: WHO Trial Registrationhttps://apps.who.int/trialsearch/NoAccess.aspx?aspxerrorpath=/trialsearch/Trial2.aspx by German Clinical Trials Register DRKS00009258, Universal Trial Number (UTN): U1111-1173-5943.